2022
DOI: 10.3389/fimmu.2022.1019115
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T cell therapy for hematological malignancies: Limitations and optimization strategies

Abstract: In the past decade, the emergence of chimeric antigen receptor (CAR) T-cell therapy has led to a cellular immunotherapy revolution against various cancers. Although CAR-T cell therapies have demonstrated remarkable efficacy for patients with certain B cell driven hematological malignancies, further studies are required to broaden the use of CAR-T cell therapy against other hematological malignancies. Moreover, treatment failure still occurs for a significant proportion of patients. CAR antigen loss on cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 199 publications
0
15
0
1
Order By: Relevance
“…While this reliance restricts off-target toxicity, it also confines their effectiveness largely to CD1d + tumors. Furthermore, loss-of-antigen relapse is a common cause of failure in CAR cell therapy ( 44 ). During CAR NKT cell treatment, tumor cells might downregulate their CD1d expression.…”
Section: Car Cells Generated From Various T Cell Subtypesmentioning
confidence: 99%
See 2 more Smart Citations
“…While this reliance restricts off-target toxicity, it also confines their effectiveness largely to CD1d + tumors. Furthermore, loss-of-antigen relapse is a common cause of failure in CAR cell therapy ( 44 ). During CAR NKT cell treatment, tumor cells might downregulate their CD1d expression.…”
Section: Car Cells Generated From Various T Cell Subtypesmentioning
confidence: 99%
“…Another primary challenge is the transient persistence of CAR NKT cells, often requiring repeat doses for sustain tumor control ( 38 ). Conventional CAR T cells benefit from design improvements, such as the tailored design of costimulatory domains, and the cytokines treatment like IL-15 ( 44 ). Similar efforts have been made for CAR NKT cells to extend their durability ( 38 , 42 ) ( Figure 1 ).…”
Section: Car Cells Generated From Various T Cell Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered T cells with a specific T cell receptor against the cancer testis antigen New York esophageal squamous cell carcinoma 1 (NY-ESO-1) have been used to treat solid tumors ( D'Angelo et al, 2018 ; Robbins et al, 2011 ). Chimeric antigen receptor (CAR) T cells that are engineered to recognize tumors and specific proteins ( June et al, 2018 ) have demonstrated strong clinical efficacy for hematologic cancers ( Huang and Huang, 2022 ) and can be modified to target other tumor types.…”
Section: Therapeutic Applications and Opportunitiesmentioning
confidence: 99%
“…Autologous (patient-derived) Chimeric Antigen Receptor T (CAR T) cells have widely proven their efficacy to treat certain B-cell haematological malignancies [1][2][3]. However, autologous CAR-T presented some limitations regarding both the manufacturing process and the use of T cell exhaust due to several therapy lines [4,5]. The possibility to use cells from healthy donors, referred to as "off-the-shelf" allogeneic CAR T or universal CAR T (UCART) could potentially overcome these limitations, as well as making a marked reduction in costs due to the implementation of industrialized manufacturing process.…”
Section: Introductionmentioning
confidence: 99%